2007
DOI: 10.1128/aac.00809-06
|View full text |Cite
|
Sign up to set email alerts
|

Poly( d , l -Lactide-Coglycolide) Particles Containing Gentamicin: Pharmacokinetics and Pharmacodynamics in Brucella melitensis - Infected Mice

Abstract: Drug delivery systems containing gentamicin were studied as a treatment against experimental brucellosis in mice. Micro-and nanoparticles prepared by using poly(D,L-lactide-coglycolide) (PLGA) 502H and microparticles made of PLGA 75:25H were successfully delivered to the liver and the spleen, the target organs for Brucella melitensis. Both polymers have the same molecular weight but have different lactic acid/glycolic acid ratios. Microparticles of PLGA 502H and 75:25H released their contents in a sustained ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 30 publications
0
42
0
1
Order By: Relevance
“…Brucella melitensis 16 M (ATCC 23456, biotype 1) smooth virulent strain was used for the different studies. Experiments were performed with fresh bacteria incubated in TSB medium at 37°C under shaking to the exponential growth phase (15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brucella melitensis 16 M (ATCC 23456, biotype 1) smooth virulent strain was used for the different studies. Experiments were performed with fresh bacteria incubated in TSB medium at 37°C under shaking to the exponential growth phase (15).…”
Section: Methodsmentioning
confidence: 99%
“…These drug delivery systems may lead to an improvement in drug cellular accumulation and a reduction of the required dosing frequency which, in turn, will improve patient compliance and the efficacy of the antimicrobial therapy. The aminoglycoside gentamicin is a bactericidal antibiotic with great in vitro activity against clinical isolates of Brucella, and it has already been encapsulated into particulated systems for the treatment of experimental brucellosis with promising results (15,16). However, the low encapsulation efficiency obtained limited the dose of particles that could be administered in vivo.…”
mentioning
confidence: 99%
“…In addition to the selective delivery to phagocytes, the ingestion of such vehicles may involve macrophage activation, and increasing the immune response of the host (22). Other advantages for antibiotic nanoparticles include enhancement of oral absorption, promotion of intracellular delivery (23)(24)(25)(26), and improvement of the antibacterial effect (27)(28)(29). Nanoparticulate systems that increase the selectivity of antibiotics in phagocytic cells have been reviewed elsewhere (19), most of which were based on biodegradable poly(lactide-co-glycolide polymer (25,28,30,31).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Lecároz et al showed that when administered in 502H micro or nanoparticles or 752H microparticles, gentamicin was successfully delivered to the liver and the spleen (85,92). Pharmacokinetic parameters illustrated the markedly altered distribution of PLGA-loaded gentamicin compared to the free drug, as higher concentrations of the antibiotic in the spleen and liver were observed when it was administered loaded in microparticles.…”
Section: Brucellosismentioning
confidence: 99%
“…The stimulation of the intracellular ROI may act synergistically with the antibiotic activity to kill intracellular bacteria, thus increasing treatment efficiency. For example, Lecároz et al studied the effect of different PLGA polymers (PLGA 502H and 752H) on the characteristics of gentamicin-containing microparticles (85). The main difference between these two polymers is the lactide/glycolide ratio, being 50:50 for the copolymer 502H and 75:25 for 752H.…”
Section: Synergy Of Polymeric Particles With Cellular Bactericidal Mementioning
confidence: 99%